Redescription of two troglobiotic species of Deuteraphorura Absolon, 1901 (Collembola, Onychiuridae) from the Western Carpathians - Parimuchová, Andrea; Kováč, Ľubomír (Zootaxa, 2016)
Two species of the genus Deuteraphorura Absolon, 1901 from the Western Carpathian caves (Central Europe) are redescribed, namely D. kratochvili (Nosek, 1963) and D. schoenviszkyi (Loksa, 1967). Both species are characterized by the absence of pseudocelli on thoracic tergum I, presence of male ventral organ on abdominal terga II–III and 3 pseudocelli on hind margin of head. D. kratochvili is redescribed based on specimens from the type locality (Demänovská Cave System) and its intraspecific variability in morphological traits is discussed. Redescription of D. schoenviszkyi (Loksa, 1967) is based on specimens from the Slovak and Aggtelek Karst, the karst area where the type locality is situated. Both species are restricted to subterranean environment, thus classified as obligate cave forms (troglobionts). An identification key to Deuteraphorura species, characterized by absence of pseudocelli on thoracic segment I, is provided.